Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian pada Platform Microstock Shutterstock di Komunitas Digital Marketing - Anggito Abimanyu; Mutya Paramita P (Teewan Journal Solutions, 2026)
The development of digital technology has transformed the landscape of visual content acquisition and utilisation. Microstock platforms such as Shutterstock facilitate global access to licensed content for various user segments. This study aims to empirically analyse the influence of price and product quality on purchasing decisions on the Shutterstock platform, with a case study of the Digital Marketing community. Using a quantitative approach through a survey method, primary data was collected from 100 respondents selected through purposive sampling. Data analysis was performed using multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study revealed contrasting findings: product quality was found to have a statistically significant influence on purchasing decisions, while price did not show a significant influence. This indicates that quality attributes such as resolution, uniqueness, aesthetics, and legality are the main determinants that consumers consider more than price when purchasing digital visual content. This study provides insights into consumer behaviour and priorities in selecting licensed visual content in the digital age.